Parent’s Communication Style in Shaping Positive Self Concept in Generation Z Adolescents in Polonia Village, Medan Polonia Subdistrict, Medan City, Sumatera Utara Province - Josua Dvp Panjaitan; Iskandar Zulkarnain; Sakhyan Asmara (Indonesian Journal of Advanced Research, 2024)
This research aims to analyze parents' communication styles in forming a positive self-concept in generation z teenagers in Polonia sub-district, as well as analyzing what factors support the formation of positive self-concept in generation z teenagers in Polonia sub-district and to find effective communication styles. in forming a positive self-concept in Generation Z teenagers in Polonia sub-district. In this research, researchers used the Communication Style theory initiated by Norton in Liliweri (2011). This research uses a qualitative approach to analyze the finding data which is then developed into research results. Researchers use data collection techniques through interviews, observation and supported by documentation. Researchers used data analysis using the Miles Huberman and Saldana method which includes data condensation, data display, and then drawing conclusions. Researchers obtained data from the Polonia sub-district, where there were more parents working in government than private sector employees, 50 were civil servants and 25 were private workers. After experiencing data saturation, the researcher involved 5 informants. The research results that researchers found were that several parents with different professional backgrounds used communication styles, including dominant style, dramatic style, open style, friendly style, attentive style, expensive style, and controversial style as dominant communication styles that shape self-concept. positive in Generation Z teenagers. In this study, researchers found communication styles that were effective in forming a positive self-concept for Generation Z teenagers, namely, Dominant Style Communication Style, Open Style Communication Style, and Friendly Style Communication Style. Then, according to the results of this research, using communication styles can form a positive self-concept in children.